Advanced photovoltaic module architecture for high value recycling and lower cost - Ruhle, Ryan J. E., author; Sampath, Walajabad, advisor; Sites, James, committee member; Weinberger, Chris, committee member (Colorado State University. Libraries, 2023)
As climate concerns continue to bolster solar energy production, the need to consider how solar panels are treated at end of life as well as the cost of solar panel production is becoming a more significant issue. Traditionally, Crystalline Silicon (c-Si) solar panels are made by laminating solar cells with glass under high heat and high mechanical pressure. The most common material used for this lamination between the glass and the c-Si solar cell is Ethylene Vinyl Acetate (EVA), a copolymer of ethylene and vinyl acetate. The first and primary issue is that it requires high temperature and a significant amount of pressure to be adhered to both the glass and the c-Si cell. Another related issue is that the c-Si cell and EVA encapsulant do not have the same thermal expansion coefficients. This leads to stresses which can cause the formation and growth of microcracks which can hinder performance and reliability of the effected solar cells. End-of-life recycling is also significantly hampered by cross-linking of EVA. The Materials Engineering Laboratory (MEL) has long worked on vacuum lamination free module architectures, though this has been primarily for use for Cadmium Telluride (CdTe) solar panels. These CdTe panels have passed IEC 61215 tests and have been applied in the field. These Edge-sealed photovoltaics modules based on Insulating Glass (IG) industry technology have many advantages including lower cost, improved manufacturability, increased durability, and enable high-value recycling with the potential for material reuse. The edge-sealed modules eliminate EVA (Ethylene Vinyl Acetate) lamination, but a gap filled with air or inert gas between the glass and solar cell increases optical reflection losses. The use of edge sealed modules for c-Si was explored in this study. A prototype manufacturing system (2 ft X 4 ft substrates) has been developed at MEL and was used in this study. Many c-Si modules were fabricated with edge sealing and were studied at the National Renewable Energy Laboratory (NREL) in various tests including accelerated tests. These studies have shown that optical reflection losses can be reduced by using nanostructures made from acrylic polymers. The nanostructures are produced by hot embossing which is intrinsically a low-cost process. The edge sealed structure has demonstrated extreme robustness to moisture ingress (5000 hrs. vs 1000 hrs. in damp heat), improved mechanical robustness, significant reduction in Potential Induced Degradation (PID), survive thermal cycling and small manufacturing footprint (80% less) while improving module reliability. The edge sealed modules have demonstrated high value recycling of the components and have the potential to make recycling of c-Si PV modules economical.